2009
DOI: 10.1016/j.juro.2009.01.104
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Specific Antigen Half-Time and Prostate Specific Antigen Doubling Time as Predictors of Response to Androgen Deprivation Therapy for Metastatic Prostate Cancer

Abstract: The results of our study suggest that prostate specific antigen half-time and prostate specific antigen doubling time after the prostate specific antigen nadir are independent prognostic indicators for an increase in prostate specific antigen after androgen deprivation therapy and cancer related death in patients with metastatic prostate cancer treated with androgen deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 20 publications
2
39
2
Order By: Relevance
“…The results of this study demonstrated that ADT patient is more likely to retain HSPC if, after PSA values reach nadir, PSA level decreases more than 0.048 ng/ml during a month, then the decrease occurs again; thus two PSA declines ≥ 0.048 ng/ml per month after nadir could be the prognostic pattern. This This finding has not been described in previous research on how different forms of PSA kinetics are associated with prognosis [5][6][7][8][9][10]. The most representative PSA prognostic patterns are pretreatment PSA, nadir, time to nadir or doubling time.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The results of this study demonstrated that ADT patient is more likely to retain HSPC if, after PSA values reach nadir, PSA level decreases more than 0.048 ng/ml during a month, then the decrease occurs again; thus two PSA declines ≥ 0.048 ng/ml per month after nadir could be the prognostic pattern. This This finding has not been described in previous research on how different forms of PSA kinetics are associated with prognosis [5][6][7][8][9][10]. The most representative PSA prognostic patterns are pretreatment PSA, nadir, time to nadir or doubling time.…”
Section: Discussioncontrasting
confidence: 54%
“…PSA has been used in therapeutic decision making by stratifying the risk of development to CRPC [4]. Characteristics of PSA variation are summarized as patterns such as pretreatment PSA level, nadir, time to nadir, and doubling time; these patterns have clinical significances as prognostic factors to predict CRPC [5][6][7][8][9][10]. However, the accuracy of these patterns as predictors is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several predictors of PFS of prostate cancer patients treated with ADT; for example, advanced age and high Gleason score for localized and locally advanced prostate cancer 19 and PSA half-time and doubling time for metastatic disease, 20 were reported previously. In the present study, we showed that the pretreatment clinical characteristics included in J-CAPRA were good predictors of PFS on univariate analysis, and clinical T and M stage on multivariate analysis.…”
Section: Discussionmentioning
confidence: 67%
“…The cohort, however, included patients with either locally advanced non-metastatic disease or metastatic disease. Park et al 17 reported that a higher PSA nadir level correlated with shorter CSS. Similar to the previous study, 16 patients with lymph node metastasis were also included.…”
Section: Discussionmentioning
confidence: 99%